PENGARUH SOCIAL MEDIA MARKETING DAN PRODUCT QUALITY TERHADAP CUSTOMER LOYALTY DENGAN BRAND IMAGE SEBAGAI VARIABLE INTERVENING (STUDI PADA PELANGGAN SERUM SKINTIFIC DI BANDUNG) - Widianti, Debora Amelia; Ramli, Rosmini (JURNAL ILMIAH EDUNOMIKA, 2024)
The purpose of this study was to examine social media marketing and product quality on customer loyalty with brand image as an intervening variable. The method used in this research is descriptive with a quantitative approach with classical assumption tests, multiple regression, sobel tests, and hypothesis testing. Data processing was carried out using the Statistical Program of Science (SPSS) version 26. The results showed that social media marketing, product quality, and brand image have a positive influence on Skintific serum customer loyalty in Bandung. Then the results of further research that social media marketing and product quality have a positive influence on the brand image of Skintific serum in Bandung. Next, the results of data processing that brand image can mediate the effect of product quality on Skintific serum customer loyalty in Bandung. However, it is different from the results of this data processing where brand image cannot mediate the effect of social media marketing on Skintific serum customer loyalty in Bandung. Keywords : Social Media Marketing, Product Quality, Customer Loyalty, Brand Image